Correction to: Health system factors influencing uptake of human papilloma virus (HPV) vaccine among adolescent girls 9-15 years in Mbale District, Uganda - Juliet Nabirye; Livex Andrew Okwi; Rebecca Nuwematsiko; George Kiwanuka; Fiston Muneza; Carol Kamya; Juliet N. Babirye (BMC, 2020)
In the original article [1] the first paragraph of the Background section was omitted due to a discrepancy between the metadata of the article and the PDF version.